mRNA Transport and Local Translation in Glia - Meservey, Lindsey Madsen (Trends Cell Biol, 2021)
Though mRNA transport and local translation are extensively studied in neurons, emerging evidence supports that these cellular processes are also abundant in non-neuronal glial cells. Here, we explore mechanisms of mRNA transport and local translation in oligodendrocytes, astrocytes, microglia, radial glia, and their functions in development, structure, and intercellular interactions.